AUTHENTIC ASSESSMENTS IN ENGLISH LANGUAGE TEACHING: A CASE IN SMP NEGERI 6 SEMARANG - Theresia Cicik Sophia Budiman; Rini Maulidhawati; Entika Fani Prastikawati (Journal of English Education and Linguistics, 2021)
The Indonesian Ministry of Education and Culture published the 2013 Curriculum which demands teachers to apply authentic assessment as the method of assessing the students’ competence. Point to that, the implementation of authentic assessment as well as its washback should be investigated. For that reason, this study is trying to investigate: (1) authentic assessments applied in English teaching and learning, (2) the types of authentic assessment used, (3) the teachers’ difficulties in applying authentic assessment, (4) washback effect of the use of authentic assessment. This study applied qualitative design to capture the implementation of authentic assessment. Observation, documentation, questionnaire, and interview were carried out to get the data. The subject are English teachers and the students. The results showed that the authentic assessment applied in English teacher class of SMP N 6 Semarang, especially in eighth grade is in the level good. The teachers had applied authentic assessments in the teaching and learning process. The types of the authentic assessments were oral interview (in speaking test), story or text retelling (in speaking), writing sample (in writing test), and experiment or demonstration. Furthermore, relating to the washback of authentic assessment, it has been confirmed by the teachers that its implementation can improves the student’s English learning achievement. On the other hand, teachers also faced some difficulties in applying authentic assessment due to their lack of knowledge of authentic assessment.